An analytical method for calculating active earth pressure in reinforced retaining walls subject to a line surcharge - Ghanbari, Ali; Taheri, Mahyar (Geotextiles and geomembranes, 2012)
Many geotechnical engineering problems require the calculation of active earth pressure behind retaining walls subject to the effect of a surcharge acting on the backfill. This study uses analytical methods to determine the pressure caused by a line surcharge on a retaining wall for reinforced backfill. The horizontal slices method is reviewed and a complete formulation of this method is proposed to determine the effect of a line surcharge on reinforced retaining walls with frictional or cohesive-frictional backfills. First, the lateral pressure from the line surcharge on walls without reinforcement is calculated and compared with those of other techniques. Then, using this formulation, an assessment is made of the active earth pressure from a line surcharge. A new formula is then proposed that considers the effect of a line surcharge on reinforcing forces and active earth pressure in reinforced fill walls. The results show that the new method accounted for the effect of cohesion and the internal friction angle of the soil on the active earth pressure from the line surcharge.